2010
DOI: 10.1192/bjp.bp.110.080051
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to standard acute in-patient care in England: roles and populations served

Abstract: Residential alternatives are integrated into catchment area mental health systems. They serve similar, but not identical, clinical populations to standard acute wards and provide some, but not all, of the functions of these wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 25 publications
(27 reference statements)
1
50
0
Order By: Relevance
“…Fatigue, exhaustion, energy loss (dissipation), social isolation, anhedonia, and regression, which are the symptoms occurring during the prognosis of depression [35] may have led to a lower social functionality level in this group. A higher mean SFS score of patients with bipolar disorder measured during admission may result from the resemblance of some symptoms such as increase in social relations, participation, anger and aggression, which are also parts of the prognosis of bipolar disorder (manic episode) [36][37][38] with features evaluated under the subdimensions of SFS [31]. Remarkably, the mean SFS score on the discharge day was lower than on the admission day of those patients with bipolar disorder, which may be due to attenuation of disease symptoms, which causes a high SFS score, by the ward atmosphere and by the effect of treatment showing a favourable result.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue, exhaustion, energy loss (dissipation), social isolation, anhedonia, and regression, which are the symptoms occurring during the prognosis of depression [35] may have led to a lower social functionality level in this group. A higher mean SFS score of patients with bipolar disorder measured during admission may result from the resemblance of some symptoms such as increase in social relations, participation, anger and aggression, which are also parts of the prognosis of bipolar disorder (manic episode) [36][37][38] with features evaluated under the subdimensions of SFS [31]. Remarkably, the mean SFS score on the discharge day was lower than on the admission day of those patients with bipolar disorder, which may be due to attenuation of disease symptoms, which causes a high SFS score, by the ward atmosphere and by the effect of treatment showing a favourable result.…”
Section: Discussionmentioning
confidence: 99%
“…Linking the model closely with community residential accommodation is a fairly common innovation: capacity to manage relatively severe crises outside hospital may be substantially greater when a 24hour staffed residential facility and a full multidisciplinary CRT work closely together (Johnson 2010). Integration of day services and CRTs has also been described and may address the criticism that patients receiving CRT care may be spending much of their days alone between team visits and may have relatively little structure to their days or activity (Allen 2009).…”
Section: Recent Innovationsmentioning
confidence: 99%
“…Populations served by these community crisis residential services overlap considerably with standard acute wards, with high proportions having previous histories of acute hospital admission and with current experiences of psychosis, although few admit people detained under the Mental Health Act. 28 Despite a long history dating back at least to the 1960s, relatively little research has examined such alternatives. However, a recent systematic review of predominantly US studies suggested that service user satisfaction may be greater than with standard wards.…”
Section: Alternatives To Standard Acute Inpatient Carementioning
confidence: 99%